Effectiveness of Four-Decontamination Techniques on Bacterial Growth on CPR Manikins after Use in a CPR Course (International Journal of First Aid Education)
The American Red Cross and American Heart Association are strong advocates of preventing disease transmission during cardiopulmonary resuscitation (CPR) training by promoting careful and consistent manikin decontamination. Because CPR is taught worldwide, identifying low-cost, efficient, and effective means of decontamination is imperative. Objective: Determine the degree of contamination on CPR manikins after routine use, and evaluate the efficacy of four disinfecting methods to reduce bacterial growth. Design: Descriptive laboratory. Setting: CPR class; microbiology laboratory. Subjects Forty-eight Actar 911™ CPR manikins (Armstrong Medical Industries, Lincolnshire, IL). Main Outcome Measure(s): Dependent variable was bacterial colony growth (count); independent variable was treatment group. Colony growths too numerous to count defaulted to a minimum 300 threshold (standard laboratory protocol). Data was analyzed with descriptive statistics and a repeated-measures ANOVA (group X time [initial, post-24, post-disinfected swab]) set a priori at 0.05. Results: A repeated-measures ANOVA revealed no significant main effect for interaction or group on mouth or chest plate swabs. Results showed a significant main effect for time on chest plate (F2,88=12.1;p<0.001) and mouth (F1.14,50.2=7.2;p=0.02) bacterial colony counts. Chest plate decreased bacterial growth from post-24 (72.8±84.9) to post-disinfected (12.2±44.6). Mouth decreased bacterial growth from initial swabbing (4.3±5.7), to post-24 (3.0±6.6), to post-disinfected (0.5±1.1). Conclusions: If unsanitized, CPR manikins are possible vectors for bacterial growth. Clorox Disinfecting Wipes™, 1:10 bleach-to-water solution and 70% isopropyl alcohol were low cost, efficient, and effective decontamination methods; UVC-light’s effectiveness requires further research. Athletic trainers and educators can use these results to appropriately select disinfecting agents to reduce risk ...